Cơ hội và thách thức của già hóa dân số cho sự phát triển bền vững ở Việt Nam - Nguyễn Thị Thu Hà (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
Population ageing is growing faster in Vietnam and characterized by a sharp increase in the number and the proportion of elderly in the population as well as the inevitable trend with both opportunities and challenges. The main task of nations in general and Vietnam in particular is not to obstruct or put off this historical progress but to face up to the reality and to actively explore strategies and countermeasures of ageing of population. By doing so, the nations can adapt to the requirements of sustainable development in order to maximize the benefits and minimize its negative influences. The main purposes of this paper are to describe the characteristics of population ageing in Vietnam, provide a review of opportunities and challenges of population ageing that pose to sustainable development in every country. This study then suggests the policies and its countermeasures from four important aspects: (1) The population policy and the efficient utilization of the elderly human resource; (2) The health care policy for the elderly; (3) The pension system reformation; and (4) The acceleration of economic growth and development in response to the population ageing as well as promoting sustainable development in Vietnam.